2007
DOI: 10.1017/s0031182007003198
|View full text |Cite
|
Sign up to set email alerts
|

Innovative chemotherapeutical treatment options for alveolar and cystic echinococcosis

Abstract: Echinococcus granulosus and Echinococcus multilocularis are cestode parasites, of which the metacestode (larval) stages cause the diseases cystic echinococcosis (CE) and alveolar echinococcosis (AE), respectively. Albendazole and mebendazole are presently used for chemotherapeutical treatment. However, these benzimidazoles do not appear to be parasiticidal in vivo against AE. In addition, failures in drug treatments as well as the occurrence of side-effects have been reported. New drugs are needed to cure AE a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 109 publications
(157 reference statements)
1
52
0
Order By: Relevance
“…Surgery is accompanied by chemotherapy, and in inoperable cases, chemotherapy is the only option. Albendazole and mebendazole are currently used (8,10). For alveolar echinococcosis, these compounds were shown to act parasitostatically rather than parasitocidally, with high recurrence rates after interruption of therapy.…”
Section: Cystic Echinococcosis Caused By Echinococcus Granulosus Ismentioning
confidence: 99%
See 2 more Smart Citations
“…Surgery is accompanied by chemotherapy, and in inoperable cases, chemotherapy is the only option. Albendazole and mebendazole are currently used (8,10). For alveolar echinococcosis, these compounds were shown to act parasitostatically rather than parasitocidally, with high recurrence rates after interruption of therapy.…”
Section: Cystic Echinococcosis Caused By Echinococcus Granulosus Ismentioning
confidence: 99%
“…For alveolar echinococcosis, these compounds were shown to act parasitostatically rather than parasitocidally, with high recurrence rates after interruption of therapy. Improved drug treatments are needed (8,24).Most countries to which malaria is endemic have now adopted artemisinin-based combination therapy as a first-line treatment for Plasmodium falciparum infection (34), and activities of artemisinins against other protozoans have been reported (1, 12). Trematodes, including schistosomes (31) and others, have proven susceptible to artemisinins and semisynthetic derivatives (13)(14)(15)(16)26), and antitumor activities of artemisinins have been reported (11,18,35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[15] Puncture, aspiration, injection, re-aspiration(PAIR) is a technique that was introduced in the mid-eighties and includes percutaneous puncture of the cyst under ultrasonic guidance, aspiration of substantial amounts of cyst fluid, injection of protoscolicidal substance (eg.95% ethanol)and re-aspiration of fluid after 5-20 min. [16] Treatment of cystic echinococcosis has been developed after a series of animal studies, both albendazole and mebendazole are considered to be equally effective [5] but other researcher concluded that albendazole is more effective than mebendazole in the treatment of hydatid cyst caused by E.granulosus and that both the intensity and the frequency of the usually mild adverse effects are comparable which including raised transaminases, abdominal pain, headache, vertigo, urticaria, jaundice. [17] Furthermore, Horton [18] mentioned that albendazole has a relatively benign safety profile with three principle areas affected (liver functions, bone marrow and hair).…”
Section: World Journal Of Pharmaceutical Researchmentioning
confidence: 99%
“…Thus benzimidazoles only prevent parasite growth, and the recurrence rates after interruption of therapy are high. Nevertheless, clinical studies have shown that chemotherapy has significantly increased the 10-year survival rate of inoperable or non-radically operated AE patients from 6-25 % to 80-83 % (Hemphill et al 2007).…”
Section: E C H I N O C O C C U S: B I O L O G Y a N D D I S E A S Ementioning
confidence: 99%